PENGARUH FOMO DAN SALES PROMOTION TERHADAP IMPULSE BUYING, DENGAN GENDER SEBAGAI VARIABEL MODERASI - Mentari Septynaputri Widodo (Jurnal Bisnis Terapan, 2024)
The rapid development of online web-based technology has significantly improved the concept of social media. The field of e-commerce has also undergone a massive evolution leading to the emergence of a new phenomenon known as Social commerce. The high development of Social commerce ultimately makes it easier for users to obtain information and makes it easier for them to shop online. This ultimately gives rise to a phenomenon called impulse buying. This study aims to examine the influence of sales promotion and FOMO on impulse buying and how gender moderate the relationship between sales promotion and impulse buying. The researcher surveyed 110 Indonesian z generation as respondents. The results show that Impulse buying and sales promotion positively affect the impulse buying, and gender moderate the relationship between sales promotion and impulse buying. This finding is line with those studies on the same topics which have conducted before in the last five years.